Reduced Mass and Diversity of the Colonic Microbiome in Patients with Multiple Sclerosis and Their Improvement with Ketogenic Diet - Swidsinski, Alexander; Dörffel, Yvonne; Loening-Baucke, Vera; Gille, Christoph; Göktas, Önder; Reißhauer, Anne; Neuhaus, Jürgen; Weylandt, Karsten-Henrich; Guschin, Alexander; Bock, Markus (Frontiers in Microbiology, 2017)
Background: Colonic microbiome is thought to be involved in auto-immune multiple sclerosis (MS). Interactions between diet and the colonic microbiome in MS are unknown. Methods: We compared the composition of the colonic microbiota quantitatively in 25 MS patients and 14 healthy controls. Fluorescence in situ hybridization (FISH) with 162 ribosomal RNA derived bacterial FISH probes was used. Ten of the MS patients received a ketogenic diet for 6 months. Changes in concentrations of 35 numerically substantial bacterial groups were monitored at baseline and at 2, 12 and 23/24 weeks. Results: No MS typical microbiome pattern was apparent. The total concentrations and diversity of substantial bacterial groups were reduced in MS patients (P<0.001). Bacterial groups detected with EREC (mainly Roseburia), Bac303 (Bacteroides), and Fprau (Faecalibacterium prausnitzii) probes were diminished the most. The individual changes were multidirectional and inconsistent. The effects of a ketogenic diet were biphasic. In the short term, bacterial concentrations and diversity were further reduced. They started to recover at week 12 and exceeded significantly the baseline values after 23-24 weeks on the ketogenic diet. Conclusions: Colonic biofermentative function is markedly impaired in MS patients. The ketogenic diet normalized concentrations of the colonic microbiome after 6 months.